Behavior of Hydrated Lipid Bilayers at Cryogenic Temperatures - Meineke, Jakob; Weik, Martin; Zaccai, Giuseppe; Fragneto, Giovanna (Frontiers in Chemistry, 2020)
Neutron diffraction was used to study the behaviour of water present in phospholipid multilamellar stacks from 1,2-Dimyristoyl-sn-glycero-3-phosphatidylcholine (DMPC) at cryogenic temperatures. Evidence was found for the existence of a highly viscous phase of water that exists between 180 and 220K based on the fact that water can leave the inter-membrane space at these low temperatures. Similar measurements are described in the literature for purple membrane (PM) samples, and from a comparison with results from this natural membrane, it is found that in the case of pure lipid samples, by using the same flash-cooling protocol, less water is trapped and the water flows out at lower temperatures, which suggests that the water is less hindered in its movements than in the PM case. It is shown that it is likely that at least the Lbeta-phase of DMPC can be frozen and that it transforms, when given enough time, to the Lc-phase only if the temperature is high enough (around 260K).